Recovery from a severe West Nile Virus infection in a one-year-old stallion following interferon alpha-2b treatment: an equine model for human therapy - McIver, Katharine (My University, 2021)
West Nile Virus (WNV) is a disease that affects both people and horses as dead-end hosts in a similar manner. Transmitted through the infected bite of a mosquito, manifestation of the disease ranges in severity from being asymptomatic to causing severe encephalitis. Therapy consists largely of supportive care, but the use of antiviral medication, such as interferon alpha-2b (INFa-2b), has been hypothesized to improve outcomes in equine cases. This case report highlights the possible benefits of administration of INFa-2b in the case of a severely neurologic young stallion infected with WNV. Greater understanding of the association of INFa-2b therapy with the outcome of equine WNV cases may provide insight into its potential use in the therapy of human WNV cases.
Keywords: West Nile Virus